Spaces of Initiation in Washington Irving’s Stories (Papers in Arts and Humanities, 2024)
America has always been a space of challenges for the ones who wanted to discover more things about it. Space becomes a special place in which destinies are made and in which man can find a proper initiation. The wish to know more about the New World pushed man to explore and assimilate the land and the cultures he encountered. American literature undertook the mission to render in symbolical terms the space in which its characters evolve. The paper will analyse two of Washington Irving's short stories, Rip Van Winkle and The Legend of Sleepy Hollow, showing how initiation can be obtained in various circumstances.
Keywords: Washington Irving; space; Puritans; identity; Transcendentalism